The Impact Of The Degree Of Adequacy Of Accounting Capital On The Financial Performance Of Banks (Applied Study On Syrian Commercial Banks Listed On The Damascus Securities Exchange) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The current research aims to test the effect of the degree of accounting capital adequacy on the financial performance of banks. The research community consists of the 14 banks registered in the Damascus Stock Exchange, but (Sham Bank, Syria International Islamic Bank, Al Baraka Bank Syria) were excluded due to the lack of full required data in their published lists.The research relied on secondary data by subtracted from the published financial statements related banks that considered the research sample on the Damascus Stock Exchange website during the period 2010-2019, which is the period whose data were available during the data collection phase.Descriptive statistics, graphs, and simple and multiple regression analysis models were used, and the stability of the variables was verified through the unit root test, and then the optimal model was chosen to analyze the relationship between the research variables.To reach the results, the E-views 10 program was used. The results of the statistical analyzes showed that there is an inverse relationship between the degree of adequacy of accounting capital and the profitability of the bank represented by (return on equity), and the absence of a relationship between the degree of adequacy of accounting capital and the profitability of the bank represented by (return on assets and return on deposits).